Cytogenetics and Molecular Genetics in Pediatric Acute Lymphoblastic Leukemia (ALL) and Its Correlation with Induction Outcomes - Ajeitha Loganathan; Rishab Bharadwaj; Arathi Srinivasan; Julius Xavier Scott (South Asian Journal of Cancer, 2022)
Abstract